Studi Keanekaragaman Invertebrata Di Kawasan Perairan Teluk Maumere Nusa Tenggara Timur - Sitti Arafah; Hastuti Juniyati (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The research objective was to determine the diversity of invertebrates in the waters of Maumere Bay, East Nusa Tenggara. This research was conducted in July-August using an exploratory descriptive approach. Sampling using purposive sampling technique. The results of the study found 150 species with descriptions: 26 species of Porifera phylum, 22 Coelenterata phylum, 67 Mollusca phylum, 5 Arthropoda phylum, and 30 Echinodermata phylum. Ecological parameters: Invertebrate density 2.05/m2-0.227/m2, relative density (RD) 0.017-0.001. The highest density value was from the type of Conus teselatus and the lowest density was from the type Aphrocallistes vastus. Frequency 0.017-0.001, relative frequency (RF) 0.015-0.001 with the highest frequency value of the Conus tesulatus type and the lowest frequency of the Aphrocallistes vastus type. The highest Importance Value Index for Conus tesulatus is 0.033 and the lowest for Aphrocallistes vastus is 0.002. The Shannon-Wiener species diversity index (H') value is 784,562 or the high richness category and the evenness value (E) is 77,856 which means that quantitatively the density value among community members is evenly distributed (E passes 1). The distribution pattern of all types of invertebrates is grouped with a Morisita Index (IM) value of 11.46-38.78 or an IM value > 1. The diversity of invertebrates in the study area is strongly influenced by environmental factors such as temperature, pH, salinity, and substrate which can reflect good conditions for the growth of invertebrates.